1997
DOI: 10.1210/endo.138.5.5134
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Transgenes in Normal and Neoplastic Anterior Pituitary Cells Using Recombinant Adenoviruses: Long Term Expression, Cell Cycle Dependency, and Effects on Hormone Secretion*

Abstract: Adenovirus vectors have recently been used to transfer genes into a variety of cell types, including neurons, glial cells, Schwann cells, and epithelial cells. To evaluate the efficiency of gene transfer into pituitary cells using viral vectors, we used replication-deficient recombinant adenovirus vectors (RAds) encoding beta-galactosidase driven by various viral promoters. We tested the ability of RAds to infect and express beta-galactosidase within the different identified cell populations of the anterior pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…To express a dominant-negative form of CREB and reporter genes we used adenovirus vectors, which have proved efficient for expressing proteins in normal pituitary cells in primary culture (3,30). To express a dominant-negative form of CREB and reporter genes we used adenovirus vectors, which have proved efficient for expressing proteins in normal pituitary cells in primary culture (3,30).…”
Section: Discussionmentioning
confidence: 99%
“…To express a dominant-negative form of CREB and reporter genes we used adenovirus vectors, which have proved efficient for expressing proteins in normal pituitary cells in primary culture (3,30). To express a dominant-negative form of CREB and reporter genes we used adenovirus vectors, which have proved efficient for expressing proteins in normal pituitary cells in primary culture (3,30).…”
Section: Discussionmentioning
confidence: 99%
“…Primary rat AP culture and biological activity studies were performed as described previously [7]. Briefly, cells were pre-incubated in DMEM containing 0.25% BSA for 2 h before the addition of conditioned medium from infected cells for 3 h. ACTH released into the culture medium was measured using a specific radioimmunoassay (RIA; NIDDK; National Hormone and Pituitary Program, Rockville, Md., USA) as described previously [8]. Immunoreactive CRH released into the culture medium and stored intracellularly was measured as described previously [7, 8].…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cells were pre-incubated in DMEM containing 0.25% BSA for 2 h before the addition of conditioned medium from infected cells for 3 h. ACTH released into the culture medium was measured using a specific radioimmunoassay (RIA; NIDDK; National Hormone and Pituitary Program, Rockville, Md., USA) as described previously [8]. Immunoreactive CRH released into the culture medium and stored intracellularly was measured as described previously [7, 8]. ACTH released from AP cells exposed to medium from HSV1/ ts K-infected cells was considered as basal release, and ACTH released from AP cells exposed to medium from ts K/CRH10-infected cells was considered as stimulated release.…”
Section: Methodsmentioning
confidence: 99%
“…Initial studies with adenoviral and herpes-derived vectors demonstrated that these two vector systems could be used to efficiently transfer different types of genes into normal rat anterior pituitary (AP) cells in primary culture as well as in the corticotropic AtT 20 and somatomammotropic GH 3 tumor cell lines [34, 35]. Interestingly, neoplastic AP cells were found to be more susceptible to viral vector-mediated transduction than were normal AP cells.…”
Section: Experimental Gene Therapy In Pituitary Tumorsmentioning
confidence: 99%